Study of occupational static magnetic field exposure among magnetic resonance scanning operators at the Azienda Ospedaliera Papa Giovanni XXIII (Bergamo) - Cretti, Fabiola Rosa; Gambirasio, A. (La Medicina del Lavoro, 2015)
Background: In this study occupational exposure to static magnetic fields of 1T and 1.5 T MR scanners installed at Azienda Ospedaliera Papa Giovanni XXIII, Bergamo, Italy, was assessed and the results were compared with the limits for worker’s exposure to static magnetic field currently applicable in Italy (Attachment 1 of D.M. 02/08/91). Objectives: The aim of the study was to assess current occupational exposure to static magnetic fields at 1T and 1.5 T MRI scanner sites and to predict exposure using the new 3 T MR equipment due to come into operation shortly. Methods: Measurements were performed sampling the static magnetic field experienced by workers while carrying out their tasks by means of a Hall effect probe. All together, 167 measurements were obtained for 29 workers (11 healthcare assistants, 14 radiography technicians and 4 anaesthesiologists). Results: The results showed wide variations of occupational exposure parameters according to the worker’s job, type of procedure and patient’s state. Nevertheless, it was possible to confirm that the regulatory limits were observed in all cases: the time spent by workers in the zone of the magnet room where B > 200 mT was much shorter than the limit of 1 hour a day prescribed by Italian law (D.M 02/08/91) and the maximum time variation of B (dB/dt) was at least 4 times lower than the value of 6 T/s taken as the health safety threshold in DM 3/8/93. Conclusions: The data collected suggest that compliance with exposure limits prescribed by Italian law will also be met with the new 3 T MR.